2007
DOI: 10.1007/s10995-007-0235-y
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Perinatal Outcomes of Adolescent Pregnancies in Cameroon

Abstract: Adolescent pregnancies are associated with both adverse fetal and maternal outcomes in Cameroon. Improving compliance with prenatal care could significantly reduce the frequency of adverse fetal outcomes in adolescent populations in Cameroon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
62
5
20

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 13 publications
18
62
5
20
Order By: Relevance
“…In addition, anemia and fever increased such a risk. Such level of childbearing by adolescents has been reported by studies done in other sub-Saharan countries: 21.1% in Zimbabwe, 24.4% in Cameroon and 24% in a multi-country study in sub-Saharan Africa [12,18,19]. This is also consistent with the distribution of teenage pregnancies in the world, the highest rates being recorded in the developing countries [1].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, anemia and fever increased such a risk. Such level of childbearing by adolescents has been reported by studies done in other sub-Saharan countries: 21.1% in Zimbabwe, 24.4% in Cameroon and 24% in a multi-country study in sub-Saharan Africa [12,18,19]. This is also consistent with the distribution of teenage pregnancies in the world, the highest rates being recorded in the developing countries [1].…”
Section: Discussionsupporting
confidence: 85%
“…In our univariate analysis adolescence was associated with LBW or PTB, as already demonstrated elsewhere [3,4,18,19,21,30,31]. Conversely studies from Nigeria and Brazil showed no association between maternal age and LBW or preterm birth [32,33].…”
Section: Discussionsupporting
confidence: 78%
“…Care during childbirth is therefore improved. 6 Our results were consistent with those of Kongnyuy et al 7 Who studied in perinatal outcomes among adolescents, they found that in addition to the number of antenatal care consultations less than four, maternal age and lack of employment were risk factors of adverse perinatal outcomes. Chiabi et al 8 identified the maternal age below 20 years, primiparity and the number of antenatal care consultations less than four as risk factors of low birth weight.…”
Section: Discussionsupporting
confidence: 92%
“…Abortus, erken doğum, hipertansiyon, anemi, yetersiz antenatal bakım, düşük doğum ağırlıklı bebekler, konjenital anomaliler, artmış sezeryan oranı, bulaşıcı hastalıklar gibi insan sağlığını tehdit eden durumların arttığı bildirilmiştir (15)(16)(17)(18). Olgumuz erken yaş hamilelik ve yetersiz antenatal bakım yüzünden sezeryan ameliyatı olmak zorunda kaldığı gibi, prematüre ve düşük doğum ağırlıklı bir bebeğe sahip olmuştur.…”
Section: Sonuçunclassified